Value chains: Answering farmers' needs - Adekunle, Adewale (Technical Centre for Agricultural and Rural Cooperation, 2012)
A mutli-purpose ICT centre in Nigeria facilitates discussion among those involved in value chains, including researchers. The approach has now expanded to more countries